2014
DOI: 10.1038/npjpcrm.2014.28
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary rehabilitation and sleep quality: a before and after controlled study of patients with chronic obstructive pulmonary disease

Abstract: Background:Poor sleep quality is common in chronic obstructive pulmonary disease (COPD). It is associated with poor quality of life. Pulmonary rehabilitation (PR) improves quality of life, exercise capacity, and anxiety and depression. Its effect on sleep quality is uncertain.Aim:To determine whether PR improves sleep quality in COPD.Methods:A prospective controlled ‘before and after’ study of sleep quality in COPD patients attending a community PR programme was conducted. Sleep quality was measured using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
(47 reference statements)
1
18
3
Order By: Relevance
“…So, the care protocol was effective in decreasing hypercapnia that consequently affected the quality of sleep. While, McDonnell, Hogg, McDonnell and White (2014) [28] stated that pulmonary rehabilitation (PR) did not improve sleep quality in COPD as indicated by the scores of Pittsburgh Sleep Quality Index (PSQI).…”
Section: Discussionmentioning
confidence: 99%
“…So, the care protocol was effective in decreasing hypercapnia that consequently affected the quality of sleep. While, McDonnell, Hogg, McDonnell and White (2014) [28] stated that pulmonary rehabilitation (PR) did not improve sleep quality in COPD as indicated by the scores of Pittsburgh Sleep Quality Index (PSQI).…”
Section: Discussionmentioning
confidence: 99%
“…It is executed in accordance with client conditions and administered using an interdisciplinary approach in order to enhance quality of life, reduce depression, increase participation in daily activities through respiration function recovery, increase respiration muscle strength, and mitigate shortness of breath 6 , 7 , 8 , 9 ) . Previous studies have shown that most respiration rehabilitation programs for patients with COPD improved the quality of life and strength of respiration muscles 6 , 7 , 8 ) , but few studies 15 , 19 ) have been conducted to determine the impact of the disease on sleep quality (which is one of the main symptoms associated with shortness of breath and/or coughing), instrumental activities of daily living, or satisfaction with leisure, which are important indices for rehabilitation. Thus, this study aimed to determine the effect of a respiration rehabilitation program on quality of sleeping, instrumental activities of daily living, and satisfaction of leisure among patients with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 59 patients with moderate to severe COPD, Lewis et al, [21] showed that Poor Sleep Quality (PSQI >5) in 61% of COPD patients regardless of their advanced age. Other two studies showed higher values (78% and 78.1%) [22,23] . However, the patients numbers in those studies was small (28 and 64 patients respectively).…”
Section: Discussionmentioning
confidence: 94%